Seeking Profits by Enhancing Older Consumer Well-Being - Moschis G.P. (2023)
Business decisions are customarily aimed at increasing profits by satisfying consumer needs and wants. Scholars have recently noted a lack of research that leads to business decisions which create positive changes and improvements in the well-being of consumers and their families. This new business orientation requires a shift in business philosophy from making profits by satisfying consumer needs and wants to making profit by creating positive changes and improvements in the consumers’ lives. To this end, business decision makers should first embrace the concept of well-being as a vehicle to achieving corporate goals, focusing on the factors that improve the well-being of customers and their families. They need to understand the factors that enhance well-being and take them into account when making business decisions. This chapter provides information on the factors that contribute to the older person’s quality of life (QOL) and increase longevity. It suggests strategies that companies could use to influence the factors that promote well-being in general and QOL in late years of life in particular. Finally, the chapter makes the reader aware of ways consumers can participate in their own transformation by taking actions that promote well-being and avoiding behaviors that impede QOL at any stage in life.